2005
DOI: 10.3390/medicina43010010
|View full text |Cite
|
Sign up to set email alerts
|

How well informed are pharmacy customers in Estonia about minor illnesses and over-the-counter medicines

Abstract: Objective. To determine how knowledgeable pharmacy customers are regarding their own health and information about minor illnesses and over-the-counter medicines.Methods. A written questionnaire was sent in the period of January to April 2003 to a sample of pharmacies in different regions of Estonia. Questionnaires were then distributed to randomly selected pharmacy customers. Of 886 questionnaires given out, 727 were answered and returned; a response rate was 82%.Results. Half of the respondents assessed their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 7 publications
2
9
0
1
Order By: Relevance
“…The results are partly supported by earlier research, where previous experience was considered important in decision making about which treatment option to select [15]. However, in Estonia, with its long tradition of the sale of medicinal plants and herbal products at community pharmacies, customers were more likely to employ pharmacists as a professional source of information.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The results are partly supported by earlier research, where previous experience was considered important in decision making about which treatment option to select [15]. However, in Estonia, with its long tradition of the sale of medicinal plants and herbal products at community pharmacies, customers were more likely to employ pharmacists as a professional source of information.…”
Section: Discussionsupporting
confidence: 69%
“…Currently in Estonian alternative medicine there are two main means of obtaining information on the use of medicinal plants: traditions or literary sources [14]. Also, some people rely on previous personal experience or information provided by a health care professional, usually a pharmacist [15],[16].…”
Section: Introductionmentioning
confidence: 99%
“…For government institutions, this can reduce costs while allowing health professionals to focus on more serious health problems (Volmer;Lilja;Hamilton, 2007). When this occurs, and when the management of these ailments is accomplished through drugs or medicinal plants, it becomes self-medication.…”
Section: Introductionmentioning
confidence: 99%
“…Our study has shown that women use more sources of information on medicines than men. The results of Estonian study (25) were the same: women were more interested in the administration, indications, side effects, interactions, and price than men. The knowledge level of male respondents was lower, and they were less willing to seek out information.…”
Section: Discussionmentioning
confidence: 80%